HUBUNGAN KEKERABATAN BAHASA MELAYU DAN BAHASA LAMPUNG - Sudirman AM; M. Ramlan; Harimurti Kridalaksana; Inyo Yos Fernandez (Humaniora, 2005)
This paper discusses the relationship between Malay and Lampung language, and attempts to answer the issue whether Lampung language is actually as old as Malay language. Malay language is considered more dominant them Lampung language, and the people are unclined to use Malay language . The result of reconstruction and comparative analyses of sound elements of lexicons indicate that Lampung language barrows and absorbs sound elements of Malay language. The status of relationship between Malay and Lampung language may be defined as languages of a family. People use Malay language to listeners outside his ethnic groups and use Lampung language on family and traditional ceremonies in the village